The slogan “One Step Ahead” As The Basis for Creating The UNESA Anthem - Karyawanto, Harpang Yudha; Mahendra, Marda Putra (Universitas Negeri Surabaya, 2025)
This article examines the creation of the UNESA anthem based on the slogan “One Step Ahead,” with the aim of strengthening the identity and spirit of Surabaya State University (UNESA) through institutional music. This song is expected to be not only a symbol of pride, but also a tool to unite the academic community with messages of progress, innovation, and togetherness. The method used is an applied creativity research design with a mixed-method approach, which includes semantic analysis of lyrics, music design, recording production, and audience perception evaluation through surveys and interviews. The results of the study show that the UNESA March song is effective in strengthening the university's image and creating strong emotional bonds among students, lecturers, and educators. The meaningful lyrics and dynamic music effectively convey motivational messages that encourage listeners to persevere and innovate. The discussion reveals that the connection between the slogan and musical elements is crucial in fostering a sense of pride and solidarity. This song has become a symbol of the university's progressive spirit, encouraging all parties to contribute to mutual achievements. The recommendation from this study is to further integrate the UNESA March song into campus life and make it part of a tradition that strengthens the university's identity. This study also provides insight for other universities to create songs of pride that reflect their values and vision.